2015
DOI: 10.1002/advs.201500089
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Near‐Infrared Photoemission in Fluoride Perovskites through Activator Aggregation and Super‐Exchange between Divalent Manganese Ions

Abstract: Biomedical imaging and labeling through luminescence microscopy requires materials that are active in the near‐infrared spectral range, i.e., within the transparency window of biological tissue. For this purpose, tailoring of Mn2+–Mn2+ activator aggregation is demonstrated within the ABF3 fluoride perovskites. Such tailoring promotes distinct near‐infrared photoluminescence through antiferromagnetic super‐exchange across effective dimers. The crossover dopant concentrations for the occurrence of Mn2+ interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 49 publications
5
93
1
Order By: Relevance
“…The lifetimes for the yellow and green emissions were estimated to be 65 and 20 ms, respectively. The yellow emission displayed a record lifetime for Mn 2+ as compared with previous reports . Interestingly, the emergence of the new emitting center has a marginal effect on the green emitting sites because it essentially showed unchanged decay kinetics (20 ms) at different doping levels of Ca 2+ (Figure S8, Supporting Information).…”
supporting
confidence: 68%
“…The lifetimes for the yellow and green emissions were estimated to be 65 and 20 ms, respectively. The yellow emission displayed a record lifetime for Mn 2+ as compared with previous reports . Interestingly, the emergence of the new emitting center has a marginal effect on the green emitting sites because it essentially showed unchanged decay kinetics (20 ms) at different doping levels of Ca 2+ (Figure S8, Supporting Information).…”
supporting
confidence: 68%
“…6a, while those samples ( x  = 0, 0.2, 0.4, 0.6) exhibit no apparent UC emissions. Since there is a large gap between the first excited state of 4 T 1 and ground state of 6 A 1 for Mn 2+ (normally > 17,000 cm −1 ) and there is no metastable excited state above 10,000 cm −1 for Yb 3+ ion2627282930, it normally requires the vicinity of Mn 2+ -Yb 3+ ions in the lattice for super exchange-interaction or cooperative sensitization based UC process. Therefore, when Mn 2+ content is high enough ( x  ≥ 0.8), the Mn 2+ ions tend to show up at the neighbor of Yb 3+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, upconversion (UC) emission of Mn 2+ could be realized by codoping Yb 3+ in the Mn 2+ doped materials27. It generally requires the vicinity of Mn 2+ -Yb 3+ ions in the lattice for superexchange-interaction or cooperative sensitization based UC process, because there is a large gap between the first excited (emissive) state 4 T 1 and the ground state 6 A 1 for Mn 2+ (normally >17,000 cm −1 ) while there is no metastable excited state above 10,000 cm −1 for Yb 3+ ion2627282930. Therefore, Mn 2+ -Yb 3+ codopants may be an option in the zeolite-Y host to check their interaction and energy transfer involved.…”
mentioning
confidence: 99%
“…Currently, research interest has concentrated on the development of cost‐effective and eco‐friendly red phosphors beyond the use of rare earth ingredients. For example, transition metal ions such as Bi 2+ , Cr 3+ , Mn 2+ , and Mn 4+ have been investigated as activator species in deep‐red‐emitting phosphors . Peng et al reported new candidates of red phosphors activated by Bi 2+ , which absorb both near‐UV and blue light and emit intense red light .…”
Section: Introductionmentioning
confidence: 99%
“…Research on Cr 3+ ion therefore mainly focuses on persistent luminescence and potential application in near‐infrared bio‐imaging or photodynamic tumor therapy . Mn 2+ single doped phosphors cannot be used for pc‐WLEDs due to their low absorption in the near‐UV or blue spectral region . In contrast with the isoelectronic Cr 3+ ion, Mn 4+ doped materials have now been widely reported for lighting, holography, laser technology, dosimetry, and optical data storage .…”
Section: Introductionmentioning
confidence: 99%